Antioxidant, analgesic and anti-inflammatory activities of the herb Eclipta Prostrate - Hossain, M.S.; Alam, M.B.; Chowdhury, N.S.; Asadujjaman, M.; Zahan, R.; Islam, M.M.; Mazumder, M.E.H.; Haque, M.E.; Islam, A. (© 2011 Academic Journals Inc., 2016)
This article was published in Journal of Pharmacology and Toxicology [© 2011 Academic Journals Inc.] and the definite version is available at: http://docsdrive.com/pdfs/academicjournals/jpt/0000/28817-28817.pdf